MODEL OF CLIMATE AND LAND-USE CHANGES IMPACT ON WATER SECURITY IN AMBON CITY, INDONESIA - Roland Alexander Barkey; Muh Faisal Mappiasse; Munajat Nursaputra (Geoplanning: Journal of Geomatics and Planning, 2017)
Ambon City is the center of national activities in Maluku province, established under Presidential Decree 77 issued in 2014 about spatial planning of Maluku Islands. Ambon is a strategic region in terms of development in agriculture and fisheries sectors. Development of the region caused this area to be extremely vulnerable to the issues on water security. Seven watersheds which are Air Manis, Hutumury, Passo, Tulehu, Wae Batu Merah, Wae Lela and Wae Sikula affect the water system in Ambon City. Therefore, this study was conducted to determine the impact of climate and land use change on water availability in seven watersheds in Ambon City. The analysis was performed using a Soil and Water Assessment Tool (SWAT) Model in order to analyze climate changes on the period of 1987-1996 (past), of 2004-2013 (present) and climate projection on the period 2035s (future) and equally to analyze land use data in 1996 and 2014. The results of the research indicated that land use in the study area has changed since 1996 to 2014. Forest area decreased around 32.45%, while residential areas and agriculture land increased 56.01% and 19.80%, respectively. The results of SWAT model presented the water availability amount to 1,127,011,350 m3/year on the period of 1987-1996. During the period of 2004-2013, it has been reduced to 1,076,548,720 m3/year (around 4.48% decrease). The results of the prediction of future water availability in the period of 2035s estimated a decrease of water availability around 4.69% (1,026,086,090 m3/year). Land use and climate change have greatly contributed to the water availability in seven watersheds of Ambon City. Ambon City is in need of land use planning especially the application of spatial plan. The maintenance of forest area is indispensable. In built-up areas, it is essential to implement green space and water harvesting in order to secure water availability in the future.